Alcance de los instrumentos de planificación territorial del municipio de Tena en la seguridad y soberanía alimentaria (2021)
The current global crisis due to the Covid-19 pandemic has shown in a more drastic way the social inequity and lack of resources for many communities in all regions of the world, which is why adaptation and development from the cities is necessary. of new political-administrative forms for the control and better functioning of commerce, industries, and service offerings; It is where the inhabitants and their families seek to settle to improve their quality of life. Due to the above, and under other premises discussed below, it is intended to carry out an analysis regarding the participation of the different planning tools of territorial entities in relation to food security and sovereignty, by specific definition of the present study for the municipality of Tena, therefore of its Territorial Ordering Scheme, of the Development Plan for the period 2020-2024, ordinances, resolutions and different public policies oriented to food sovereignty and security, carrying out a proposal that as defined in The study is about evaluating the "Scope of the Territorial Planning Instruments of the Municipality of Tena in Food Security and Sovereignty".